(untitled) (Islas, 2021)
The present work constitutes an investigation whose general objective is to assess the historical and patrimonial significance of the La Aurora de Matanzas newspaper between 1828 and 1857. Theoretical methods such as the analytical-synthetic, inductive-deductive and historical-logical were used. Empirical methods were also employed like a bibliographic and documentary review, and a content analysis. Among the results, it was found that the La Aurora de Matanzas newspaper contributed to the conformation of Matanzas’ Public Communication System between 1828 and 1857, mainly because it introduced improvements in the printing press, and changes in the typography, and it used a great variety of sections and themes.